2018
DOI: 10.1002/nbm.3868
|View full text |Cite
|
Sign up to set email alerts
|

Can T1w/T2w ratio be used as a myelin‐specific measure in subcortical structures? Comparisons between FSE‐based T1w/T2w ratios, GRASE‐based T1w/T2w ratios and multi‐echo GRASE‐based myelin water fractions

Abstract: Given the growing popularity of T -weighted/T -weighted (T w/T w) ratio measurements, the objective of the current study was to evaluate the concordance between T w/T w ratios obtained using conventional fast spin echo (FSE) versus combined gradient and spin echo (GRASE) sequences for T w image acquisition, and to compare the resulting T w/T w ratios with histologically validated myelin water fraction (MWF) measurements in several subcortical brain structures. In order to compare these measurements across a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 42 publications
1
54
0
Order By: Relevance
“…Previous studies have suggested that myelin is the predominant source of MR contrast in T1‐weighted and T2‐weighted images (Bock, Kocharyan, Liu, & Silva, ; Eickhoff et al, ; Laule et al, ; Wallace et al, ), and by using the ratio of these images the contrast sensitivity to detect myelin content is increased further due to attenuation of the shared intensity biases (Glasser & Van Essen, ). Although, other studies have questioned the sensitivity of the T1‐w/T2‐w ratio for myelin content, and argued that it is likely not the only factor contributing to the T1‐w/T2‐w image (Arshad et al, ; Righart et al, ; Uddin et al, ). Still, it has been shown that T1‐w/T2‐w ratio differentiates between high and low myelinated cortex as determined by myelin proteolipid protein staining (Nakamura et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that myelin is the predominant source of MR contrast in T1‐weighted and T2‐weighted images (Bock, Kocharyan, Liu, & Silva, ; Eickhoff et al, ; Laule et al, ; Wallace et al, ), and by using the ratio of these images the contrast sensitivity to detect myelin content is increased further due to attenuation of the shared intensity biases (Glasser & Van Essen, ). Although, other studies have questioned the sensitivity of the T1‐w/T2‐w ratio for myelin content, and argued that it is likely not the only factor contributing to the T1‐w/T2‐w image (Arshad et al, ; Righart et al, ; Uddin et al, ). Still, it has been shown that T1‐w/T2‐w ratio differentiates between high and low myelinated cortex as determined by myelin proteolipid protein staining (Nakamura et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In disorders with a strong demyelinating component such as multiple sclerosis (MS), the T1‐w/T2‐w ratio is lowered in pathologically vulnerable regions (Beer et al, ; Nakamura, Chen, Ontaneda, Fox, & Trapp, ). However, recent studies have raised controversy on the interpretation of the T1‐w/T2‐w ratio, showing that this measure may also reflect tissue microstructure other than myelin, such as axon and dendrite density or iron content (Arshad, Stanley, & Raz, ; Righart et al, ; Uddin, Figley, Marrie, & Figley, ; van Rooden et al, ). Because disrupted brain connectivity is an important feature of AD (Dicks et al, ; Fornito et al, ; Pievani et al, ), an intracortical reduction of myelin content in AD could be hypothesized.…”
Section: Introductionmentioning
confidence: 99%
“…Resultantly, it has been suggested T1w/T2w is a less than optimal index of white matter myelin (Arshad et al, 2016;Uddin et al, 2018).…”
Section: Methodological Considerations and Limitationsmentioning
confidence: 99%
“…One prominent technique is myelin water imaging (MWI), which exploits the different T2-relaxation times of water trapped between myelin sheaths, yielding a myelin water fraction (MWF) parameter (MacKay et al, 1994;Uddin et al, 2018). The accuracy of MWI has been validated in studies correlating histopathological myelin samples and neuroimaging-derived MWF in animal (Beaulieu et al, 1998 (Laule et al, 2006(Laule et al, , 2008.…”
Section: Possible Biological and Functional Correlatesmentioning
confidence: 99%
See 1 more Smart Citation